EFFECTS OF SAWAH TECHNOLOGY ON THE GROWTH AND YIELD PERFORMANCE OF NERICA RICE VARIETIES IN THE SOUTH-EAST NIGERIA: EFFECTS OF SAWAH TECHNOLOGY ON THE GROWTH AND YIELD PERFORMANCE OF NERICA RICE (Nigerian Journal of Technology, 2022)
Field experiment research was conducted to determine the effects of Sawah Technology on NERICA rice production from April to December 2020 during the rainy season at two different locations, namely, Ishieke and ImeohaNkerefi in Ebonyi State and Enugu State respectively, both in the south-east of Nigeria. Six NERICA rice varieties: Sipi692033, WITA 4, NERICA 34, NERICA 1, NERICA 7 and NERICA 19 were used for the study on two Sawah fields and two non-Sawah fields measured 0.3ha each. Research data, namely: height, width, panicle length, grain number, and grain weight were collected starting from nursery to maturity of the rice. The study revealed that Sipi692033 has the highest yield of 5 tons/ha under Sawah Technology condition. The findings of the study show that the panicle length, grain number per panicle, weight of 1000 grains, and yield (ton/ha) were higher by 55.56 %, 50.00 %, 39.41 %, and 87.50 % respectively in the Sawah field relative to the non-Sawah field. The study concludes that Sawah technology enhances rice yield by at least 50 per cent.